2018
DOI: 10.1111/apa.14227
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of neonatal conjunctivitis evaluated in a population‐based setting

Abstract: Chlamydia trachomatis was a rare pathogen in neonatal conjunctivitis in a population-based setting, but respiratory viruses were detected more frequently than indicated earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
1
9
0
3
Order By: Relevance
“…We therefore used the feline albumin qPCR assay described by Helfer-Hungerbuehler et al to quantify feline genome equivalents (used as a proxy for host cell yields) [ 50 ]. The use of flocked swabs resulted in higher host cell yields compared to cytology brushes, which is in line with previous studies where flocked swabs were successfully used for detecting ocular chlamydial infections in pigs [ 35 ] and humans [ 38 ]. We did not investigate whether using either sampling device had an effect on the chlamydial detection rate; therefore, the biological relevance of our finding is unclear.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We therefore used the feline albumin qPCR assay described by Helfer-Hungerbuehler et al to quantify feline genome equivalents (used as a proxy for host cell yields) [ 50 ]. The use of flocked swabs resulted in higher host cell yields compared to cytology brushes, which is in line with previous studies where flocked swabs were successfully used for detecting ocular chlamydial infections in pigs [ 35 ] and humans [ 38 ]. We did not investigate whether using either sampling device had an effect on the chlamydial detection rate; therefore, the biological relevance of our finding is unclear.…”
Section: Discussionsupporting
confidence: 85%
“…Due to the obligate intracellular nature of Chlamydiaceae , sufficient numbers of host cells must be collected in the sampling process to ensure detection of the pathogen. In previous studies, cytology brushes were often reported as collection devices for conjunctival samples, but flocked swabs have been successfully used as well [ 13 , 35 , 36 , 37 , 38 ]. Yet, some authors claimed that cytology brushes appear to collect more cells and would therefore be associated with increased detection rates [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comparable bacterial growth pattern were also observed by others. [ 4 ] Since there was no instillation of prophylactic antibiotic drops after delivery, the cause for conjunctivitis in our study could not have been due to chemicals. Chlamydia as a cause of conjunctivitis was ruled out clinically in our study because all the infants had conjunctivitis within 1–5 days after birth, there was no pseudo-membrane formation, and there was no history of sexually transmitted diseases among the mothers.…”
Section: Discussionmentioning
confidence: 98%
“…IM: intramuscular; IV: intravenous. Most studies conducted in recent decades agree that there has been a change in the microbial etiology of NC 10,11,15,18,[24][25][26][27] , from microorganisms acquired through the birth canal (N. gonorrhoeae and C. trachomatis) to microorganisms of the skin and upper respiratory tract 10,28 .…”
Section: Discussionmentioning
confidence: 99%